Challenges in accepting the e-learning system: the case of e-learners from different backgrounds of study - Md Nor, Mohd Zakhiri; Mohamad, Ani Munirah (2013)
While the world could see the significance of the e-learning system in providing access to the education system due to its simplicity, convenience and low cost, the situation at the end of the bargain is the impact of the e-learning system on the e-learners themselves.The scenario is further complicated by the fact that the e learners could come from various academic backgrounds, different from the current e-learning courses they are taking. It is within this context that this paper aims to critically examine the challenges in accepting the e-learning system within the context of e-learners who possess academic backgrounds different that the e-learning course they are taking up.In addition, this research aims to propose recommendations for the betterment of the e-learning system, particularly by taking into consideration the viewpoints of the respondents, who are the educators,. the system developer and the e-learners themselves.The research adopts a qualitative method, comprising of the collection of primary data (which involves a field work adopting the case study design on a private global university in Malaysia) and secondary data (which involves a library-based research).The primary data which have been generated is analysed by using the computer aided qualitative data analysis software ATLAS-ti version 6.2 prior to reporting of the same.The paper concludes that the acceptance of the e-learning system is generally motivated by the technology acceptance theory which emphasizes upon the perceived usefulness and perceived ease of use of the system.Nevertheless, the case is not so similar for e learners who come from academic backgrounds different than the course they are taking up as there are challenges facing their acceptance of the e-learning system.